School Strategies for Flood-Prone Primary Schools in the Districts of Bendahara and Banda Mulia in Aceh Tamiang Regency - Walidaini walidaini; Najmuddin Najmuddin; Munawar Munawar (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
This study examines the strategic management strategies utilized by primary schools in flood-prone regions in Aceh Tamiang Regency, Indonesia. The study seeks to investigate how educational leaders devise, execute, and assess management measures to maintain learning continuity during persistent flooding events. A qualitative case study methodology was utilized to gather data via in-depth interviews, direct observations, and document analysis at two public elementary schools located in the Bendahara and Banda Mulia Districts. Data were examined with NVivo 12 software to discern prevailing themes and managerial trends. The results indicate that school resilience is cultivated through three interconnected strategic elements: proactive planning, adaptive implementation, and reflective evaluation. Proactive planning emphasizes risk identification, the incorporation of flood mitigation strategies into educational policies, and preparedness training for educators and students. Adaptive implementation prioritizes flexible learning structures, community collaboration, and the use of local resources during floods. Reflective evaluation encompasses participatory dialogues, peer assessments, and continuous enhancement to bolster institutional preparedness. The study indicates that efficient disaster-responsive school management necessitates visionary leadership, collaborative planning, and robust community engagement. The findings enhance the theoretical discussion on resilient educational management by illustrating how context-specific techniques might support teaching and learning in disaster-prone areas.